Potensi Pendirian Baitul Maal Wat Tamwil (BMT) Kecamatan Batang Angkola Kebupaten Tapanuli Selatan - Mardia Khairani; Fatahuddin Aziz Siregar; Delima Sari Lubis (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2020)
Abstract The presence of BMT as a microfinance institution is very much needed by the community, because most people become micro-entrepreneurs, so with this encouragement, researchers are interested in researching the potential for establishing BMT, namely in Hutatonga Village, Batang Angkola District, South Tapanuli Regency because there are no financial institutions in that area yet. using sharia principles. While the purpose of this study was to determine the potential for establishing BMT in Hutatonga Village, Batang Angkola District, South Tapanuli Regency. This research is a descriptive qualitative research type, and to collect the required data used data collection instruments consisting of interviews conducted directly with informants. The results showed that the Hutatonga Village had the potential to establish BMTs. This potential is that there are strengths in the establishment of BMTs in the Hutatonga village, namely the process of establishing them is easy, provides benefits, has reach to small businesses and the weakness is that they are not yet popular among the community, human resources are still weak, the systems and procedures that regulate are not standardized. Keywords: Potential, BMT, SWOT